USO DA MAQUETE COMO RECURSO DIDÁTICO PARA O ENSINO DE GEOGRAFIA - MAX PEREIRA CARDOSO (2024)
Modern education is constantly seeking innovative methods to make teaching more dynamic and accessible, especially in Geography. This paper aims to explore the use of models as a teaching tool to facilitate the understanding of relief and altimetry, exemplified by the construction of a model of the municipality of Miranda/MS. To this end, planning and model making procedures were carried out, linking theory and practice through the choice of materials and hypsometric representation, aiming to facilitate the understanding of geographic concepts, stimulating the interaction of students with the content. The model is an effective resource to connect geographic knowledge to the reality of students, providing meaningful and active learning. The data obtained allowed the development of a teaching plan to assist teachers during Geography classes. Therefore, this material will help students to understand the altimetric aspects of the region where they live, and will serve as a basis for future work.